A study on friction and axial effects in PELLET-CLAD mechanical interaction - Harriague, Santiago; Meyer, John E. (Comisión Nacional de Energía Atómica; Argentina, 1982)
Fil: Harriague, Santiago Comisión Nacional de Energía Atómica; Argentina